Upscaling impact of wind/sea surface temperature mesoscale interactions on southern Africa austral summer climate. (5th August 2018) - Desbiolles, Fabien; Blamey, Ross; Illig, Serena; James, Rachel; Barimalala, Rondrotiana; Renault, Lionel; Reason, Chris
Abstract : Mesoscale sea surface temperature (SST) variability plays an important role in shaping local atmospheric boundary layers through thermodynamic processes. This study focuses on the upscaling effects of mesoscale SST gradients in sensitive areas on the southern Africa regional atmospheric circulation. Using regional atmospheric model sensitivity experiments which differ only in the mesoscale SST forcing characteristics (either the full spectrum of SST variability or only its large‐scale components are included), we first quantify the importance of SST gradients on regional atmospheric conditions. Agulhas eddies and meanders influence the vertical air column up to the troposphere, and mesoscale ocean patterns significantly modify incoming landwards moisture fluxes. The austral summer mean state is then modified in terms of air temperature, cloud cover and mean rainfall, with notable differences in tropical rainbands over southwestern Africa. Mesoscale SST variability favours tropical–extra‐tropical interactions and cloudband development over the continent. These results stress the importance of high‐resolution ocean forcing for accurate atmospheric simulations. Abstract : Snapshot of SST (°C) on December 4, 2008 for the Ctrl (a) and noMeso‐SST (b) forcing fields. (c) One‐month (January 2009) average of daily wave number spectra (°C 2 ) of ~5 km resolution original (bold line) and smoothed (dashed line) OSTIA SST computed over the WRF domain (a). For comparison, theoretical profiles in k −2 and k −4 are drawn (thin lines). (d) Binned scatterplot of 10 m wind speed perturbations (m/s) versus OSTIA SST perturbations (°C) for observed QuikSCAT and Ctrl run outputs in grey and red, respectively. Analysis is performed over DJF months using 15‐day SST and wind speed running averages over the Agulhas region (black frame in (a)). Each bin represents a 1/200 of the central 95% of the distribution. The bars indicate ±1 SD about the average drawn with bold line. Spatial perturbations are isolated from large‐scale features using a Lanczos filter with 2D‐half‐power filter cut‐off wavelengths of 10°